2006
DOI: 10.1175/jcli4045.1
|View full text |Cite
|
Sign up to set email alerts
|

PDO–ENSO Effects in the Climate of Mexico

Abstract: The role of the Pacific decadal oscillation (PDO) in El Niño–Southern Oscillation (ENSO)-related Mexican climate anomalies during winter and summer is investigated. The precipitation and mean temperature data of approximately 1000 stations throughout Mexico are considered. After sorting ENSO events by warm phase (El Niño) and cold phase (La Niña) and prevailing PDO phase: warm or high (HiPDO) and cold or low (LoPDO), the authors found the following: 1) For precipitation, El Niño favors wet conditions during su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 16 publications
8
85
0
13
Order By: Relevance
“…The PDO climate pattern was described by Zhang et al (1997) and Mantua et al (1997). Many authors have reported strong relationships between the Pacific climate features and climate, hydrology and ecology (Knox and Lawford, 1990;Francis and Hare, 1994;Francis et al, 1998;Bonsal and Lawford, 1999;Hare et al, 1999;Overland et al, 1999;Dettinger and Diaz, 2000;Bond and Harrison, 2000;Brito-Castillo et al, 2003;Pavia et al, 2006). The PDO index as developed by Hare (1996) and Zhang (1996), and used by Mantua et al (1997), is the leading principal component (PC) from an un-rotated empirical orthogonal function analysis (EOFA) of monthly "residual" sea surface temperature anomalies, poleward of 20°N for the 1900-1993 period of record.…”
Section: The Pacific Decadal Oscillation: a Primermentioning
confidence: 99%
“…The PDO climate pattern was described by Zhang et al (1997) and Mantua et al (1997). Many authors have reported strong relationships between the Pacific climate features and climate, hydrology and ecology (Knox and Lawford, 1990;Francis and Hare, 1994;Francis et al, 1998;Bonsal and Lawford, 1999;Hare et al, 1999;Overland et al, 1999;Dettinger and Diaz, 2000;Bond and Harrison, 2000;Brito-Castillo et al, 2003;Pavia et al, 2006). The PDO index as developed by Hare (1996) and Zhang (1996), and used by Mantua et al (1997), is the leading principal component (PC) from an un-rotated empirical orthogonal function analysis (EOFA) of monthly "residual" sea surface temperature anomalies, poleward of 20°N for the 1900-1993 period of record.…”
Section: The Pacific Decadal Oscillation: a Primermentioning
confidence: 99%
“…This analysis of PDO projections for 2000-2050 shows a multi-model mean shift towards more occurrences of the negative phase PDO. Some form of the correlates or effects of a multi-model mean result of more negative phase PDO-like conditions for the early 21st century may be apparent throughout the North Pacific Basin, as long as the PDO's regional teleconnections maintain stationarity (Mantua and Hare, 2002;Deser et al, 2004;Pavia et al, 2006). In general, this shift towards more negative PDO-like conditions in the North Pacific Basin will be superimposed upon the general global warming trend and its meridional pattern of differing effects from hydrological cycle intensification, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…tropical storms, tropical easterly waves, inverted troughs, the Madden Julian Oscillation, and mid-latitude troughs) and bring above-average precipitation across much of Mexico (Douglas et al, 2007;Wang et al, 2007). Subtle changes to the position and strength of these circulation features appear to be connected to global scale shifts in circulation patterns related to changes in sea surface temperature patterns (e.g., El Niño-Southern Oscillation) affecting rainfall variability of Mexico at inter-annual timescales and can persist for years (e.g., the Pacific Decadal Oscillation, PDO), bringing extended periods of unusually wet or dry conditions at decadal timescales (Magaña et al, 2003;Pavia et al, 2006).…”
Section: Rainfall Distribution Over Mexicomentioning
confidence: 99%
“…For example (see Figures 6a & b), the prolonged 1940-55 and 1996-onward dry periods in mean total annual precipitation over the C and N domains (early dry period lasting longer in the N domain until 1960, while the actual dry period started earlier in the C domain in 1980); the moderate 1960-1980 wet period between dry periods and the earlier wet period that ended in 1940 over both domains are evidence that wet and dry periods can affect more than half of the country at the same time, affecting not only mean total annual precipitation but also mean total seasonal precipitation (see Figures 6e, f, i & j). These multi-decadal annual and seasonal fluctuations in time series of N and C domains are linked to the PDO shifts, from cold to warm PDO in the mid-1970s and from warm to a temporarily cold PDO at the end of the 1990s (Pavia et al, 2006). Moreover, in the northwestern portion of the N-domain (known as the monsoon region, Higgins et al, 2003), it is known that winter precipitation is in phase with the PDO (Brito-Castillo et al, 2002;Pavia et al, 2006).…”
Section: Regionalizationmentioning
confidence: 99%
See 1 more Smart Citation